IMPLIKASI AKTIVITAS PUASA BAGI UMAT HINDU (PERSPEKTIF TEOLOGI SOSIAL) - Komang Heri Komang Yanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
ABSTRACTFasting is actually a very beneficial activity for Hindus. Because, it can not be avoided if self-control is the main element in fasting. Religious teachings always teach a people to be able to control themselves. Self-control can be understood through fasting. Realization in the community shows that fasting or upawasa has not been ingrained in the hearts of the Hindu community. This is also because they do not know the meaning of fasting well. For this reason, socialization about fasting is still very much needed, both through written and oral socialization. Fasting is not the end of a struggle for worship. However, fasting is precisely the starting point of a human being to start a new life, because through learning self- control in fasting activities, one will be able to resist the next temptation. One of the lessons of fasting can also be seen as planting social solidarity with the suggestion of doing as much good as possible. Religious people should learn to curb egoism, greed, and violence. Thus a person is able to open his love.Keywords: Self Qualities, Hindus, Fasting.